DERADIKALISASI DOKRIN AGAMA: MENELAAH ULANG INTERPRETASI AMAR MAKRUF NAHI MUNGKAR DALAM AL-QUR’ÂN - Taufik Akbar; Hepni Putra; Ica Fauziah Husnaini (IAT IAIN Pontianak, 2022)
This paper started from the increasingly-massive radicalism movement in the name of religion nowdays. The tendency of radical acts in religious discourse refered to various understandings of normative texts, such as jihad discourse, enforcement of Islamic law, and enforcement of amar ma'ruf nahi munkar. This paper specifically re-analyzed the relation of religious radicalism with the discourse of amar ma'ruf nahi munkar which was understood literally, especially with sources of understanding that refered to the normative text of the Qur'an. This paper concludes that there are norms that must be seen and put forward in enforcing the command of amar makruf nahi mungkar, such as the universalimse values of Islam about peace, promoting moderation and tolerance, and also paying attention of the signs set by the State on the other side.